Bernard Shaw : Compete Playes with Prefaces (Volume V) - Published by Dodd, Mead & Company (New York Dodd, Mead & Company, 1962)
Playwright, wit, socialist, polemicist, vegetarian and charmer, Shaw was a controversial literary figure, the scourge of Victorian values and middle-class pretensions. Holroyd has cut his huge biography to a manageable single-volume life - the definitive Shaw for general readers and students alike.
Includes Illustrations , Appendix and Index
Keywords: Shaw, Bernard, 1856-1950 -- Dramatists, Irish -- Dramatists, English